Cooperative non‐orthogonal multiple access with SWIPT over Nakagami‐m fading channels. Issue 5 (31st January 2019) - Kader, Md. Fazlul; Uddin, Mohammed Belal; Islam, Anik; Shin, Soo Young
Abstract: To meet with both the energy and spectral efficiency, cooperative non‐orthogonal multiple access (NOMA) (termed as CNOMA) and simultaneous wireless information and power transfer (SWIPT) are integrated in this paper. Two different protocols such as CNOMA‐SWIPT‐PS and CNOMA‐SWIPT‐TS are proposed, by employing power‐splitting (PS) and time‐switching (TS) energy harvesting (EH) techniques, respectively. In the proposed protocols, a base station (BS) directly communicates with a NOMA near user, whereas the communication with a NOMA far user is performed with the assistance of an energy‐constrained relay node. The relay node harvests energy from the transmitted signal by the BS, employing PS or TS EH technique. We investigate ergodic sum capacity and outage probability of the proposed protocols along with analytical derivations over Nakagami‐ m fading channels. Finally, the effectiveness of the proposed schemes over existing strategy and conventional multiple access is demonstrated through analysis and simulation. Abstract : To meet with both the energy and spectral efficiency, cooperative non‐orthogonal multiple access (NOMA) (termed as CNOMA) and simultaneous wireless information and power transfer (SWIPT) are integrated in this paper. We investigate ergodic sum capacity and outage probability of the proposed protocols along with analytical derivations over Nakagami‐ m fading channels. Finally, the effectiveness of the proposed schemes over existing strategy and conventional multiple access is demonstrated through analysis and simulation.